2016
DOI: 10.1016/j.exger.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and energetics in rodent longevity research

Abstract: The impact of calorie amount on aging has been extensively described; however, variation over time and among laboratories in animal diet, housing condition, and strains complicates discerning the true influence of calories (energy) versus nutrients on lifespan. Within the dietary restriction field, single macronutrient manipulations have historically been researched as a means to reduce calories while maintaining adequate levels of essential nutrients. Recent reports of nutritional geometry, including rodent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 97 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…Median lifespan variations of up to 31% (704-925 days) have been observed for a single mouse strain housed and fed under identical conditions in collaborating laboratories, and strain and sex differences can modify responses to dietary restriction, which is known to extend the lifespan. Furthermore, the food intake of mice, which in turn can affect lifespan, is greater when animals are held in rooms at temperatures lower than their thermoneutral zones (30-34°C) [75]. Oxidative Medicine and Cellular Longevity…”
Section: Discussionmentioning
confidence: 99%
“…Median lifespan variations of up to 31% (704-925 days) have been observed for a single mouse strain housed and fed under identical conditions in collaborating laboratories, and strain and sex differences can modify responses to dietary restriction, which is known to extend the lifespan. Furthermore, the food intake of mice, which in turn can affect lifespan, is greater when animals are held in rooms at temperatures lower than their thermoneutral zones (30-34°C) [75]. Oxidative Medicine and Cellular Longevity…”
Section: Discussionmentioning
confidence: 99%
“… 2010 ). As such, a large body of research has focused on using the DR paradigm to try to understand the mechanisms underlying variation in aging and lifespan (e.g., Gems and Partridge 2012 ; Fontana and Partridge 2015 ; Gibbs and Smith 2016 ). However, the evolutionary basis of the response has been much less well investigated (Raubenheimer et al.…”
mentioning
confidence: 99%
“…For instance, a well-described, long-lived mouse strain was utilized for these studies, but of a single inbred genotype and level of CR (40% restriction). Although 40% CR has been shown to increase life span in some but not all study conditions reported (1,13,16,47), a more recent report indicated a nonlinear, sex-dependent dose-effect differential with two levels of CR (20% vs 40% restriction), with 20% CR being superior for longevity benefits under the conditions tested (15). However, improvements in glucose homeostasis have been reported with levels of CR up to 40% (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although both acarbose treatment and CR alter glucose metabolism and homeostasis, both interventions also induce significant changes in gastrointestinal (GI) function. With CR generally reported to have positive glucoregulatory and longevity effects within studies in both sexes, albeit with exceptions (13)(14)(15)(16), versus the sex-biased benefits of acarbose more toward males, we hypothesized differences in metabolomic profiles may contribute to these sex-differential effects. A high-dimensional metabolomics platform was utilized to assess treatment and sex effects on >600 metabolites using C57BL/6 inbred mice randomized to control, CR, or acarbose (0.1%, ACA) treatment, including both tissue-directed responses with liver samples and a measure of GI-related effects through cecal contents coincident with the treatment.…”
mentioning
confidence: 99%